MILTEFOSINE IN TREATMENT OF OLD WORLD CUTANEOUS LEISHMANIASIS IN PAKISTAN: Miltefosine in Treatment of Cutaneous Leishmaniasis - Dar, Brig Nasser Rashid; Rehman, Simeen Ber; Abbas, Muhammad; Amjad, Muhammad; Mashhood, Asher Ahmed; ., Qamar; Ranjha, Khalid; Rao, Sibghat Ullah (Pakistan Armed Forces Medical Journal, 2010)
Objective: To evaluate the efficacy of miltefosine in the treatment of cutaneous leishmaniasisStudy Design: Uncontrolled, open label, quasi-experimental studyPlace and Duration of Study: The study was carried out in Military Hospital Rawalpindi and five other Army Hospitals from Jan 2006 to Aug 2006.Patients and Methods: This study was dome to investigate the efficacy of treatment of cutaneous leishmaniasis patients with oral miltefosine in doses of 2.5 mg/kg/day at 6 centers in Pakistan. The study was conducted among 90 hospitalized adult cutaneous leishmaniasis patients. All patients completed the full 28-days treatment course.Results: The study revealed excellent response in 32(28.8%), good in 38(34.4%), fair in 17(15.3%) and poor in 3(2.7%) patients. Treatment-related adverse events were transient rise in ALT (95%), followed by myalgia (33%), arthralgia (15%), nausea vomiting (12%), bad oral taste (2%), testicular pain (4%), cough (2%), conjunctivitis (2%) and fever (1%). All theses side effects were transient and settled on discontinuation of medication. Compliance was goodConclusion: The use of oral miltefosine in doses of 2.5 mg/kg/day is effective & well tolerated in old world cutaneous leishmaniasis.